Cationic Chains of Phosphanyl‐ and Arsanylboranes1. Issue 14 (3rd March 2014) - Marquardt, Christian; Thoms, Christine; Stauber, Andreas; Balázs, Gábor; Bodensteiner, Michael; Scheer, Manfred
Abstract Whilst catena‐phosphorus cations have been intensively studied in the last years, mixed Group 13/15 element cationic chains have not yet been reported. Reaction of the pnictogenboranes H2EBH2⋅NMe3 (E=P, As) with monohalideboranes lead to the cationic chain compounds [Me3N⋅BH2EH2BH2⋅NMe3][X] (E=P, As; X=AlCl4, I) and [Me3N⋅BH2PH2BH2PH2BH2⋅NMe3][X] (X=I, VCl4(thf)2), respectively. All of the compounds have been characterized by X‐ray structure analysis, NMR spectroscopy, IR spectroscopy, and mass spectrometry. DFT calculations elucidate the reaction pathway, the high thermodynamic stability, the charge distribution within the chain and confirm the observed solid‐state structures.